Managing Cross-Functional Cooperation for New Product Development Success - Gemser, Gerda; Leenders, Mark A.A.M. (Long range planning, 2011)
This article focuses on conditions that make cross-functional cooperation in new product development projects more or less productive. We investigate 40 NPD projects in the consumer electronics and pharmaceuticals industries in which R&D and marketing played key roles. We find that the contributions of cross-functional cooperation to NPD success are contingent on the type of market and technology opportunities being pursued. More specifically, our results suggest that when a project team pursues an opportunity characterized by high levels of technological and market risks, investments in high levels of cross-functional cooperation are warranted to increase NPD success. We do not find evidence that cross-functional cooperation moderates the relationship between the openness of an NPD project towards external information and knowledge and its performance. This suggests that less integrated project teams could achieve similar results as more integrated teams in terms of processing large quantities of information and knowledge without incurring the costs that may stem from high levels of cross-functional cooperation.